Understanding Students' Intention to Use Mobile Learning at Universitas Negeri Semarang: An Alternative Learning from Home During Covid-19 Pandemic - Ismiyati Ismiyati; Badrun Kartowagiran; Muhyadi Muhyadi; Mar'atus Sholikah; Suparno Suparno; Tusyanah Tusyanah (LED Edizioni Universitarie, 2021)
Coronavirus Disease (Covid-19) pandemic influenced education systems throughout the world, including in Indonesia. It makes the universities and schools go online for their teaching-learning process. Therefore, mobile learning can be an alternative solution to carry out the teaching and learning process as suggested by the government. The purpose of this study was to explore empirically mobile learning acceptances based on Technology Acceptance Model (TAM) with satisfaction as the mediating variable. The population of this study is 250 Economics Education students at Universitas Negeri Semarang. The sample was taken by purposive sampling with the criteria of students who have used mobile learning in supporting their learning activities. Structural Equation Model (SEM) with AMOS 24 was performed to analyze quantitative data. The results showed that from 6 hypotheses, there are 5 accepted hypotheses; they are; perceived ease of use, perceived usefulness, and perceived interactivity have positive and significant effects on the intention to use mobile learning. The mediating variable (satisfaction) is successful to strengthen the influence between perceived ease of use and intention; and perceived usefulness and intention. However, satisfaction is rejected to mediate perceived interactivity and intention to use. Stakeholders should improve students' satisfaction in their learning activities. The limitation of this study was the research results cannot be easely generalized in other contexts. In the future, other researchers can add other factors to examine better technology acceptance.